Challenges of civic engagement in the (post-socialist) transitional society: experiences from waterfront urban areas Mezapark in Riga and Kalarand in Tallinn - Prilenska, Viktorija; Paadam, Katrin; Liias, Roode (Journal of Architecture and Urbanism, 2020)
Current case studies examine the shortcomings of civic engagement strategies during the design process and ratification of detailed plans for urban areas of strategic importance − Mezapark in Riga and Kalarand in Tallinn. Detailed plans caused public outcries and led to long-lasting and distressful negotiations between local communities, developers, designers and municipalities over the future development and use of these areas. The debates about detailed plans raised an increasing public interest in planning related issues and growing demands for greater civic engagement in decisions shaping the city. At the same time, the debates demonstrated the inability of local planning frameworks to meet public expectations. There appears a salient need for changing the planning culture. This paper studies the shortcomings of civic engagement strategies and the desirable changes through a series of semi-structured interviews with key stakeholders involved and the analysis of planning related documentation.